ESG Integration in SOE Directors' Duties: Comparing Indonesian and Malaysian Corporate Law - Alia Imron (Siyasah Dusturiyah: State Law Review, 2026)
This article comparatively analyzes the integration of Environmental, Social, and Governance (ESG) mandates into the fiduciary duties of State-Owned Enterprise (SOE) directors in Indonesia and Government-Linked Companies (GLC) in Malaysia. Utilizing a normative doctrinal approach, this study addresses the systemic tension between ESG transition risks and directors' personal liability. In Indonesia, the rigid state finance doctrine often criminalizes SOE business losses, creating a chilling effect on sustainable investments. Conversely, Malaysia treats GLCs as private entities, evaluating failures through civil mechanisms unless decisions are "plainly wrong". To resolve these specific jurisdictional asymmetries, this research actively proposes the novel concept of an "ESG-linked BJR Safe Harbor". The study concludes that courts must definitively elevate ESG compliance from a mere administrative reporting obligation into a highly objective judicial standard, successfully validating it as material evidence of good faith to formally activate the Business Judgment Rule protections for corporate fiduciaries globally and domestically today.